Bias in Subject Access Standards: A Content Analysis of the Critical Literature - Olson, Hope A.; Schlegl, Rose (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
This paper reports the results of a content analysis of the literature on biases in classification and subject headings. This study gathers 93 works documenting biases of gender, sexuality, race, age, ability, ethnicity, nationality, language and relations with the goals of : 1) identifying existing research and experience on subject access for marginalized groups and to marginalized topics. . .